Liquid biopsy evaluation of circulating tumor DNA, miRNAs, and cytokines in meningioma patients - Aran, Veronica; Lyra Miranda, Renan; Heringer, Manoela; Carvalho da Fonseca, Anna Carolina; Andreiuolo, Felipe; Chimelli, Leila; Devalle, Sylvie; Niemeyer Filho, Paulo; Moura-Neto, Vivaldo (Frontiers in Neurology, 2024)
Introduction Liquid biopsy is a non-invasive method used to detect cancer and monitor treatment responses by analyzing blood or other bodily fluids for cancer biomarkers. Meningiomas are the most common primary central nervous system tumors, and biomarkers play a crucial role in their diagnosis, prognosis, and treatment monitoring. The World Health Organization (WHO) classifies meningiomas based on tumor grades and molecular alterations in genes such as in NF2, AKT1, TRAF7, SMO, PIK3CA, KLF4, SMARCE1, BAP1, H3K27me3, TERT promoter, and CDKN2A/B. Liquid biopsy, specifically cell-free DNA (cfDNA) analysis, has shown potential for monitoring meningiomas as it can detect ctDNA release in the blood, unaffected by the blood-brain barrier. MicroRNAs (miRNAs) have also been found to be deregulated in various cancers, including meningiomas, presenting potential as diagnostic biomarkers. Additionally, studying cytokines in the tumor microenvironment may aid in establishing prognostic or diagnostic panels for meningiomas. Methods In the present study we analyzed the DNA coming from both the plasma and tumor samples, in addition to analyze miRNA-21 and cytokines in the plasma of 28 meningioma patients. Discussion and Conclusion Our findings indicate that the detection of ctDNA in the plasma of meningioma patients is feasible. However, it's important to note that certain challenges persist when comparing plasma DNA analysis to that of tumor tissues. In our study, we observed a paired identification of mutations in only one patient, highlighting the complexities involved. Furthermore, we successfully identified miR-21 and cytokines in the plasma samples. Notably, our analysis of Interleukin 6 (IL-6) unveiled higher expression in the clear cell subtype compared to the other types. Despite the ongoing research, the clinical implementation of liquid biopsy in meningiomas remains somewhat limited. Nevertheless, our promising results underscore the need for further investigation.